Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Genomic insights into the transition from saprophytic to parasitic lifestyles in Hymenochaetales - Ji-Hang Jiang; Xue-Wei Wang; Zi-Qi Shen; Qiu-Shi Li; Shi-Liang Liu; Li-Wei Zhou (Molecular Phylogenetics and Evolution, 2026)

Interlayer solution fissure flows as important and stable recharge sources for epikarst springs: evidence from isotopic measurements and in situ observations - Chunmao Shi; Qiuwen Zhou; Yuan Li; Hang Yang; Ze Yuan; Jian Qiu; Zhanghong Li; Dequan Zhou; Shengtian Yang (Journal of Hydrology, 2026)

Gut bacterial degradation of food-grade iota-carrageenan enhances its pro-inflammatory activity - Ruya Ji; Xiaoqing Li; Xiaojing Guo; Zhenjun Zhu; Zhichang Qiu; Pongpol Thanuphol; Yanhui Han; Hang Xiao (Food Bioscience, 2026)

Retraction notice to “Light absorption of black carbon and brown carbon in winter in North China Plain: comparisons between urban and rural sites” [Sci. Total Environ. 770 (2021) 144821] - Jiaxing Sun; Conghui Xie; Weiqi Xu; Chun Chen; Nan Ma; Wanyun Xu; Lu Lei; Zhijie Li; Yao He; Yanmei Qiu; Qingqing Wang; Xiaole Pan; et al. (Science of The Total Environment, 2026)

Parametrization and improvement of the soil evaporation estimation model: Coupling superposition based on fractional canopy cover and soil moisture - Xuefeng Qiu; Xiaoyang Liang; Hang Wang; Jiandong Wang; Guoli Li; Lei Zhang; Hao Zhang; Dingtian Zhou; Xurong Mei (Journal of Hydrology, 2026)

Triple-synergy Strategy for High-phosphorus-retention High-temperature Proton Exchange Membranes at 40–160 °C for Fuel Cell - Linjian Sang; Qian Wang; Panlong Zhou; Heguo Han; Jianhang Qiu; Xi Sun; Hang Zhang; Guorui Qin; Jifu Zheng; Shenghai Li; Suobo Zhang (Chemical Engineering Journal, 2026)

Dynamic landslide susceptibility assessment in Zhouqu County, China, based on SBAS-InSAR and a Stacking ensemble learning model - Xingyao Guan; Peng Chen; Hang Liu; Zheng Li; Liangcai Qiu; Chengchang Zhu; Yang Hong; Yibin Yao; Zufeng Li (Advances in Space Research, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Comparative Proteomic Insights into Low Molecular Weight Chitosan-Induced Drought Tolerance in Sugarcane - Gui Zhou; Xiao-Xia Liu; Li-Hang Qiu; Cheng-Lin Zou; Yang-Rui Li (Sugar Tech, 2026)

Dynamical modelling and vibration dissipation of monopiles for offshore wind turbine with multiple prestressed tuned mass dampers under multi-hazard excitations - Zhenbo Lei; Gang Liu; Weiguo Li; Qingshan Yang; Jianxin Zhang; Hang Li; Zheng Qiu (Ocean Engineering, 2026)

Flow-driven regulation of CaCO3 precipitation and fracture evolution in heterogeneous fractures - Tengfei Ma; Hang Deng; Puxuan Kang; Yuchao Feng; Xiaofan Yang; Liang Zhao; Xueying Li; Dexi Wang; Xingming Chen; Zhengmao Yang; Weisheng Qiu; Junfeng Ji; et al. (Geochimica et Cosmochimica Acta, 2026)

Host-associated volatile cues drive foraging behavior of Trichopria drosophilae toward Drosophila suzukii-infested fruits - Hai-Kuan Sun; Fan Yang; Ze-Hua Wang; Ren Li; Guang-Hang Qiao; Qiu-Fei Li; Yu-Yu Wang; Shan-Ning Wang (Journal of Pest Science, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Economic benefits of carbon source selection for polyphosphate-accumulating organisms in enhanced biological phosphorus removal - Jing Yuan; Liping Chen; Xiaojing Xie; Hang Chen; Xiaodong Du; Acong Chen; Haixin Zheng; Fu Huang; Sijia Ji; Zemin Li; Xianghui Liu; Zhiyi Deng; et al. (Environmental Research, 2026)

In situ therapeutic vaccine gel induces pyroptosis and remodels tumor microenvironment to prevent postoperative hepatocellular carcinoma recurrence and metastasis - Liangdi Jiang; Faisal Raza; Shiqi Yang; Kunwei Li; Hang Xiao; Wenjing Chen; Jing Su; Mingfeng Qiu (Chemical Engineering Journal, 2026)

Thrombectomy in Stroke Patients with Large Vessel Occlusion and Mild Symptoms: Insights from a Multicenter Observational Study - Kai Qiu; Yu Hang; Penghua Lv; Ying Liu; Mingchao Li; Liandong Zhao; Qijin Zhai; Jinan Chen; Zhenyu Jia; Yuezhou Cao; Linbo Zhao; Haibin Shi; et al. (Translational Stroke Research, 2025)

Microbial transformation of Fenton sludge to crystalline iron minerals with fermentation-derived phosphorous for heavy metal immobilization - Han Li; Zhangyi Xu; Tsung-Yi Chen; Fangyuan Meng; Hang Chen; Chengshuai Liu; Guanglei Qiu; Chunhua Feng (Journal of Hazardous Materials, 2025)

Bimetallic ion crosslinked hydrogels sequentially releasing immunomodulatory factors and osteogenic factors to promote bone integration of 3D printed titanium alloy prostheses - Xiao Sheng; Zhenjia Che; Chuncheng Shen; Jingtao Wu; Chenhao Qiu; Chenjie Tan; Junjie Mao; Bo Li; Hang Yu; Jianyou Li; Wei Liu; Chen Li; et al. (Chemical Engineering Journal, 2025)

Phototrophic microalgae-driven comprehensive remediation of arsenic and cadmium: A novel iron mineralization pathway enabling arsenic immobilization - Daijie Chen; Guobao Wang; Taicong Liu; Chiyu Chen; Zekai Feng; Yuanyuan Jiang; Hang Yu; Mengyao Li; Jean Louis Morel; Yuanqing Chao; Yetao Tang; Shizhong Wang; et al. (Journal of Cleaner Production, 2025)

The “Coexistence” of Ehrlich pathway and de novo pathway improves 2-PE synthesis in Saccharomyces cerevisiae - Chenghan Yang; Qingqing Lv; Li Zhang; Huining Jia; Hailong Chen; Sainan Yang; Yuxin Qiu; Haifeng Hang; Ali Mohsin; Ju Chu; Yingping Zhuang; Xiwei Tian (Chemical Engineering Journal, 2025)

Trace element and sulfur isotope study of sulfide chimneys from the mafic-hosted Daxi Vent Field: Implications on the genesis of seafloor massive sulfide deposit at a segment end - Yejian Wang; Ming Yang; Xiqiu Han; Sven Petersen; Yiyang Cai; Xinkai Hu; Anxia Chen; Zhongyan Qiu; Xing Yu; Hang Hu; Matthias Frische; Honglin Li (Chemical Geology, 2025)

Vertically oriented micron-thick perovskite film enables efficient and stable inverted perovskite solar cells - Bing-Hao Lv; Yong-Chun Ye; Jun-Gan Wang; Liu-Jiang Zhang; Yu-Hang Zhang; Ming-Li Zheng; Xian-Min Chen; Hui-Wei Du; Jie Yang; Xin-Yu Zhang; Meng-Lei Xu; Qiu-Feng Ye; et al. (Chemical Engineering Journal, 2025)

Investigation on the influence of the transverse jet on a self-propelled submarine - Hang Guo; Peng Li; Lianzhou Wang; Ke Qiu (Ocean Engineering, 2025)

Numerical simulation on the effects of jet in crossflow on the wake uniformity of the submarine - Hang Guo; Peng Li; Lianzhou Wang; Ke Qiu; Zhihao Ma (Ocean Engineering, 2025)

Magma evolution along detachment fault-affected ridge segments: Petrology and geochemistry of MORBs from the Tianxiu segment, Carlsberg Ridge - Hang Hu; Xing Yu; Xiqiu Han; Jiqiang Liu; Yejian Wang; Zhongyan Qiu; Tong Zong; Honglin Li; Xucheng Xu; Hu He (Lithos, 2025)

The PHD transcription factor ThPHD5 regulates antioxidant enzyme activity to increase salt tolerance in Tamarix hispida - Yao-Shuo Tan; Jing-Hang Li; Pei-Long Wang; Dan-Ni Wang; Bai-Chao Liu; Sonethavy Phetmany; Yong-Xi Li; Qing-Jun Xie; Cai-Qiu Gao (Plant Science, 2025)

Sevoflurane postconditioning mitigates neuronal hypoxic-ischemic injury via regulating reactive astrocytic STAT3 protein modification - Yufei Jia; Yanhong Song; Hang Xue; Xingyue Li; Yinong Zhang; Shiyue Fan; Xu Yang; Zixuan Ding; Yue Qiu; Ziyi Wu; Ping Zhao (Chemico-Biological Interactions, 2025)

Effects of Dietary Chlorogenic Acid on the Growth, Lipid Metabolism, Antioxidant Capacity, and Non-Specific Immunity of Asian Swamp Eel (Monopterus albus) - Hang Yang; Chengcheng Wu; Quan Yuan; Weiwei Lv; Junqiang Qiu; Mingyou Li; Qinghua Zhang; Wenzong Zhou (Fishes, 2024)
To investigate the dietary effects of chlorogenic acid (CGA) on the growth performance, lipid metabolism, antioxidant activity, and non-specific immunity of Asian swamp eel (Monopterus albus) during the domestication stage, a 28-day feeding experiment was conducted to supplement with CGA at levels of 0 (Cont.), 250 (CGA 0.50%), 500 (CGA 1.00%), and 750 (CGA 1.50%) mg/kg·bw by feeding with yellow mealworm (Tenebrio molitor). Compared with the control group, the addition of 250–750 mg/kg of CGA significantly increased the weight-gain rate (WG) of M. albus, and the CGA 1.0% group displayed the highest value. The content of hemoglobin and high-density lipoprotein in all CGA groups was markedly elevated (p

Candidatus Thiothrix phosphatis SCUT-1: A novel polyphosphate-accumulating organism abundant in the enhanced biological phosphorus removal system - Liping Chen; Xuhan Deng; Xiaojing Xie; Kaiying Wang; Hang Chen; Sheqi Cen; Fu Huang; Cenchao Wang; Yaqian Li; Chaohai Wei; Guanglei Qiu (Water Research, 2024)

Multi-touch microcapsules/silicone-polyacrylate hybrid hydrogels with precise self-healing ability and their self-powered sensing applications in emergency rescue - Bingqian Zhao; Xiaolong He; Wenjian Li; Hang Zhang; Han Liu; Hua Qiu; Peng Gu; Kunlin Chen (Chemical Engineering Journal, 2024)

Engineering optimal gold nanorod-loaded hollow mesoporous organosilica nanotheranostics for NIR-II photoacoustic microscopy imaging and tumor synergistic therapy - Xin Li; Xuehan Wang; Hongrui Qiu; Shiying Li; Lik Hang Hugo Tse; Wai-Sum Lo; Kwok-Ho Lui; Haiyu Zhou; Yanjuan Gu; Wing-tak Wong (Chemical Engineering Journal, 2024)

Enhanced gut microbiota delivery of a model probiotic (Faecalibacterium prausnitzii): Layer-by-layer encapsulation using riboflavin-conjugated sodium alginate and glycol chitosan - Bo Qiu; Huijuan Jing; Shengyi Han; Shuobo Zhang; Furong Ba; Lvwan Xu; Siyuan Xie; Wang Gao; Yilun Huang; Hang Xiao; David Julian McClements; Björn Berglund; et al. (Food Hydrocolloids, 2024)

Relating the carbon sources to denitrifying community in full-scale wastewater treatment plants - Jinling Chen; Xia Tang; Xuewei Wu; Biping Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Xuhan Deng; Xiaojing Xie; Chaohai Wei; et al. (Chemosphere, 2024)

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

Infiltration simulation and system design of biogas slurry drip irrigation using HYDRUS model - Haitao Wang; Hang Wang; Xiaoyang Liang; Jiandong Wang; Xuefeng Qiu; Chuanjuan Wang; Guangyong Li (Computers and Electronics in Agriculture, 2024)

Iron–doped bismuth oxybromides as visible−light−responsive Fenton catalysts for the degradation of atrazine in aqueous phases - Yong-Li Cai; Yu-Hang Xu; Ji-Zun Xiang; Zhi-Qiang Zhang; Qiu-Xiang He; Ya-Feng Li; Jian Lü (Journal of Environmental Sciences, 2024)

Organic anion transporting polypeptide 3a1 is a novel influx pump for Perfluorooctane sulfonate in Sertoli cells and contributes to its reproductive toxicity - Ting Li; Lianlian Jiang; Shaokai Zheng; Chong Qiu; Nannan Zhao; Xiaojun Lin; Hang Ren; Jiyan Huang; Hongxia Wang; Lianglin Qiu (Chemosphere, 2023)

Candidatus Accumulibacter use fermentation products for enhanced biological phosphorus removal - Liping Chen; Gengrui Wei; Yushen Zhang; Kaiying Wang; Cenchao Wang; Xuhan Deng; Yaqian Li; Xiaojing Xie; Jinling Chen; Fu Huang; Hang Chen; Bin Zhang; et al. (Water Research, 2023)

Seismic responses of super high-rise buildings under long-period ground motions - Zi-Hang Zhang; Qiu-Sheng Li (Engineering Structures, 2023)

Mechanism of arsenic immobilization and biotransformation in the biological aqua crust of mine drainage - Chiyu Chen; Guobao Wang; Mengyao Li; Xiaoting Chen; Daijie Chen; Zekai Feng; Yuanyuan Jiang; Hang Yu; Yuanqing Chao; Yetao Tang; Rongliang Qiu; Shizhong Wang (Science of The Total Environment, 2023)

The interplay between microalgae and toxic metal(loid)s: mechanisms and implications in AMD phycoremediation coupled with Fe/Mn mineralization - Daijie Chen; Guobao Wang; Chiyu Chen; Zekai Feng; Yuanyuan Jiang; Hang Yu; Mengyao Li; Yuanqing Chao; Yetao Tang; Shizhong Wang; Rongliang Qiu (Journal of Hazardous Materials, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Ca–La layered double hydroxide (LDH) for selective and efficient removal of phosphate from wastewater - Yuhang Cao; Xuewei Wu; Biqing Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Chaohai Wei; Jian Wei; Guanglei Qiu (Chemosphere, 2023)

Effect of bioaugmentation on tetracyclines influenced chicken manure composting and antibiotics resistance - Can Wang; Yinxue Jia; Jianpeng Li; Yu Wang; Huan Niu; Hang Qiu; Xing Li; Weizhen Fang; Zhongping Qiu (Science of The Total Environment, 2023)

Nitrogen−doped−CQDs/schwertmannites as visible−light−responsive Fenton catalysts for the degradation of chlortetracycline and related cytotoxicity - Yu-Hang Xu; Xiang-Ji Liu; Ji-Zun Xiang; Zhi-Qiang Zhang; Xing-Xing Qiao; Ya-Feng Li; Qiu-Xiang He; Jian Lü (Journal of Cleaner Production, 2023)

Prospective pyroxenite–peridotite mixed mantle source for the northern Carlsberg Ridge - Hang Hu; Xing Yu; Xiqiu Han; Yejian Wang; Zhongyan Qiu; Tong Zong; Jiqiang Liu; Honglin Li; Xucheng Xu (Lithos, 2023)

One-step fabrication of self-healing poly(thioctic acid) coatings on ZE21B Mg alloys for enhancing corrosion resistance, anti-bacterial/oxidation, hemocompatibility and promoting re-endothelialization - Zhao-Qi Zhang; Pei-Duo Tong; Li Wang; Zheng-Hui Qiu; Jing-An Li; Hang Li; Shao-Kang Guan; Cun-Guo Lin; Hong-Yan Wang (Chemical Engineering Journal, 2023)

Association between pyrethroid exposure and risk of depressive symptoms in the general US adults - Hui-ru Li; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Science and Pollution Research, 2023)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Phthalate exposure enhances incidence of urinary incontinence: US NHANES, 2003–2004 and 2005–2006 - Xianyanling Yi; Kun Jin; Shi Qiu; Xingyu Xiong; Tianyi Zhang; Ge Peng; Dazhou Liao; Xiaonan Zheng; Hang Xu; Hong Li; Lu Yang; Qiang Wei; et al. (Environmental Science and Pollution Research, 2022)

Biflavonoids from the twigs and leaves of Cephalotaxus oliveri Mast. and their α -glucosidase inhibitory activity - Min Song; Tong Xiao; Qiu-Shuang Wu; Hang Fai Kwok; Ging Chan; Li-Gen Lin; Xiao-Qi Zhang; Wen-Cai Ye; Sheng-Jiang He; Qing-Wen Zhang (Natural Product Research, 2022)

Two new compounds from a mangrove sediment-derived fungus Penicillium polonicum H175 - Shun-Zhi Liu; Xi-Xiang Tang; Feng-Ming He; Jian-Xin Jia; Hang Hu; Bao-Ying Xie; Ming-Yu Li; Ying-Kun Qiu (Natural Product Research, 2022)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Inhibition of Candida albicans and induced vaginitis by sapindus water extract - Lu Li; Jindan Qiu; Minping Wei; Yunfei Xie; Hang Yu; Yahui Guo; Yuliang Cheng; Weirong Yao (Natural Product Research, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Clinical characteristics and plasma antibody titer of patients with COVID-19 in Zhejiang, China - Wei-ling Xiang; Jing-jing Cheng; Lian-peng Wu; Bing-yu Chen; Wen-xin Li; Dan-ying Qiu; Wei Zhang; Fei-hang Ge; Dong Chen; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Antibacterial activity and mechanism of ThDP analogs against rice brown stripe pathogen Acidovorax avenae subsp. avenae RS-1 - Xiao Xuan Wang; Hang Ying Qi; Jie Chen; Ying Zi Yang; Wen Qiu; Wei Wang; Peng Zou; Bin Li; Yan Li Wang; Hong Wu He; Guo Chang Sun (Journal of Plant Pathology, 2019)

Genetic diversity, genetic structure and migration routes of wild Brassica juncea in China assessed by SSR markers - Xiao-Qin Sun; Yan-Qiu Qu; Mi-Mi Li; Xiao-Ling Song; Yue-Yu Hang (Genetic Resources and Crop Evolution, 2018)

Characteristics of polycyclic aromatic hydrocarbons in PM2.5 emitted from different cooking activities in China - Yun-Chun Li; Jia-Qian Qiu; Man Shu; Steven Sai Hang Ho; Jun-Ji Cao; Ge-Hui Wang; Xian-Xiang Wang; Xiao-Qing Zhao (Environmental Science and Pollution Research, 2018)

Characteristics analysis of spatial and temporal variation on extreme weather events in Anhui Province for recent 50 years - Jun Zhao; Jinchao Xu; Xuechun Li; Yi Zhong; Donghao Han; Hang Qiu (Natural Hazards, 2017)

Hybrid electrooxidation and adsorption process for the removal of ammonia in low concentration chloride wastewater - Jing Ding; Qing-Liang Zhao; Jun Zhang; Jun-Qiu Jiang; Wei Li; Hang Yu; Li-Kun Huang; Yun-Shu Zhang (Environmental Science and Pollution Research, 2017)

Selenocystine-induced cell apoptosis and S-phase arrest inhibit human triple-negative breast cancer cell proliferation - Meijun Long; Juekun Wu; Junwen Hao; Wei Liu; Yong Tang; Xi Li; Hang Su; Wanshou Qiu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Impacts of the Wenchuan earthquake on tree mortality and biomass carbon stock - Shuai Qiu; Ming Xu; Yunpu Zheng; Renqiang Li; Michelle Hang Gi Wong; Liyun Zhang; Lixiang Liu; Changhong Lai; Wen Zhang (Natural Hazards, 2015)

Induction of female 2n gametes and creation of tetraploids through sexual hybridization in cassava (Manihot esculenta) - Hang-Gui Lai; Xia Chen; Zheng Chen; Jian-Qiu Ye; Kai-Mian Li; Jin-Ping Liu (Euphytica, 2015)

Proteomic Analysis of Osmotic Stress-Responsive Proteins in Sugarcane Leaves - Gui Zhou; Li-Tao Yang; Yang-Rui Li; Cheng-Lin Zou; Li-Ping Huang; Li-Hang Qiu; Xing Huang; Manoj Kumar Srivastava (Plant Molecular Biology Reporter, 2012)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Exercise benefits cardiovascular health in hyperlipidemia rats correlating with changes of the cardiac vagus nerve - You-Hua Wang; Hao Hu; Sheng-Peng Wang; Zhen-Jun Tian; Quan-Jiang Zhang; Qiu-Xia Li; You-You Li; Xiao-Jiang Yu; Lei Sun; Dong-Ling Li; Bing Jia; Bing-Hang Liu; et al. (European Journal of Applied Physiology, 2010)

A Novel Camptothecin Derivative Incorporated in Nano-Carrier Induced Distinguished Improvement in Solubility, Stability and Anti-tumor Activity Both In Vitro and In Vivo - Min Han; Cai-Xia He; Qiu-Li Fang; Xiao-Chun Yang; Yuan-Yuan Diao; Dong-Hang Xu; Qiao-Jun He; Yong-Zhou Hu; Wen-Quan Liang; Bo Yang; Jian-Qing Gao (Pharmaceutical Research, 2009)